Prognostic value of volume-weighted mean nuclear volume in canine mast cell tumours - Martins, Mafalda Casa Nova da Costa (2019)
Cutaneous Mast Cell Tumour (cMCT)’s Patnaik and Kiupel grading schemes rely on qualitative and semi-quantitative features susceptible to bias and inter-observer variability. The stereological estimation of volume-weighted mean nuclear volume (VV), on the other hand, provides information about both nuclear size and its variability, proven to have prognostic value in many solid tumours. VV of 55 cMCTs was estimated using the point-sampled intercept method in 10 microscopic fields (800 X). These tumours were graded by three pathologists and the final grade was compared with VV and clinical history of dogs with a follow-up period of one year. A cut-off value of VV>168 μm³ was shown to differentiate aggressive cMCTs with 78.3% specificity and 87.5% sensitivity. The present study suggests that the estimation of VV on routine histological sections may objectively improve the detection of more aggressive cMCTs; Resumo: Valor Prognóstico do Volume Nuclear Médio em Mastocitomas Caninos A gradação de Mastocitomas Cutâneos Caninos (cMCTs) pelo sistema de Patnaik e Kiupel é baseado em critérios qualitativos e semi-quantitativos, que estão sujeitos a viés e variabilidade inter-observador. O recurso ao princípio estereológico do ‘volume médio nuclear’ (VV), por outro lado, fornece simultaneamente informação sobre o tamanho nuclear e a sua variação, o que está associado a um valor de prognóstico em diversos tumores. O VV de 55 cMCTs foi estimado através do método ‘point-sampled intercept’ em 10 campos microscópicos (800 X). Estes tumores foram classificados por três patologistas e a classificação final foi comparada com o VV e o follow-up clínico de um ano. Um cut-off de VV>168 μm³ revelou diferenciar cMCTs de comportamento mais aggressivo com uma especificidade de 78.3% e uma sensibilidade de 87.5%. Este estudo sugere que o VV poderá objectivamente auxiliar a detecção de cMCTs com um comportamento mais agressivo.